2020
DOI: 10.1186/s13063-020-04435-7
|View full text |Cite
|
Sign up to set email alerts
|

Overall adjustment acupuncture for postmenopausal osteoporosis (PMOP): a study protocol for a randomized sham-controlled trial

Abstract: Background: Osteoporosis is becoming more prevalent in aging societies worldwide, and the economic burden attributable to osteoporotic fractures is substantial. The medications presently available to treat osteoporosis have side effects. Acupuncture is widely used for treating osteoporotic postmenopausal women because it is non-invasive and has fewer side effects, but the powerful clinical evidence for its efficacy remains insufficient. Our study intends to explore the effect of overall adjustment acupuncture … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Recently, Shi et al 33 found that catgut embedding at acupoint has a good effect on PMOP by improving BMD and alleviating participants' clinical problems. Overall adjustment acupuncture can improve the level of hormones that play an antideterioration role, correct disturbances of osteogenic and adipogenic activity of bone marrow mesenchymal stem cells, improve mineral density by activating osteoblast synthesis, minimize pain, decline incidence of fractures, and improve the general quality of life of osteoporotic postmenopausal women 34 . Acupuncture can normalize estrogen levels, which enhances calcium deposition and slows the rate of bone degeneration 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Shi et al 33 found that catgut embedding at acupoint has a good effect on PMOP by improving BMD and alleviating participants' clinical problems. Overall adjustment acupuncture can improve the level of hormones that play an antideterioration role, correct disturbances of osteogenic and adipogenic activity of bone marrow mesenchymal stem cells, improve mineral density by activating osteoblast synthesis, minimize pain, decline incidence of fractures, and improve the general quality of life of osteoporotic postmenopausal women 34 . Acupuncture can normalize estrogen levels, which enhances calcium deposition and slows the rate of bone degeneration 35 .…”
Section: Discussionmentioning
confidence: 99%
“…However, these results were obtained from studies on non-human subjects, and evidence in human subjects is lacking. Our ongoing clinical trial was designed to collect data, including estradiol levels, in patients with PMOP upon OA treatment to cover this gap ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…OA has been shown to improve the clinical symptoms and quality of life in patients with osteoporosis ( 23 ). A systematic and comprehensive clinical study is also being conducted by our team to study the efficacy, safety, and mechanism of OA in patients with PMOP to provide more rigorous clinical evidence to promote its application ( 24 ). In the present study, we investigated the anti-osteoporotic effect of OA and explored its mechanism of action through endocrine modulation in a rat model of PMOP induced by bilateral ovariectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of osteoporosis in women in China over 50 years of age is 32.1% and 51.6% in over 60. With the aging of the global population, the global incidence of osteoporosis in postmenopausal women was 50% and the incidence of fracture was 40% in the population of postmenopausal women, 3 severely decreasing the quality of life and increasing the morbidity in old women. Thus, it is important to screen and diagnose PMOP in time to reduce the disease burden.…”
Section: Introductionmentioning
confidence: 99%